Implementation of a community‐based hypertension control program in Matanzas, Cuba - Valdés González, Yamilé; Campbell, Norm R.C.; Pons Barrera, Edelys; Calderón Martínez, Marcy; Pérez Carrera, Alina; Morales Rigau, José Manuel; Afonso de León, Jose Alberto; Pérez Jiménez, Vivian; Landrove Rodríguez, Orlando; DiPette, Donald J.; Giraldo, Gloria; Orduñez, Pedro (The journal of clinical hypertension (Greenwich, Conn.), 2020)
Increased blood pressure is a leading risk factor for death worldwide, and improving the control of hypertension is a major health goal to reduce non‐communicable disease. Thus, in 2016, as part of a regional effort between the Pan American Health Organization and Cuban Ministry of Public Health to reduce cardiovascular risk and disease, a community demonstration project was implemented to enhance hypertension control. The intervention project was in a population of 25 868 people served by the Carlos Verdugo Martínez Polyclinic in Matanzas, Cuba. The project implemented interventions currently recommended in the World Health Organization HEARTS modules, including a standardized clinical training program with certification for blood pressure measurement, routine screening for hypertension in clinics and in the community, a simple directive pharmacologic treatment algorithm, and a registry with performance reporting and feedback. Qualitative and quantitative program monitoring and evaluation was established. In a 2010 national survey, the prevalence of hypertension and the rate of hypertension control were estimated to be 31% and 36%, respectively. Following less than one year of the full implementation of the program, the prevalence of hypertension, proportion of the hypertensive population registered as having hypertension, proportion of those drug‐treated who were controlled, and estimated population rate of control were 30%, 90%, 68%, and 58%, respectively. Based on these positive results, the program has been expanded to include another demonstration program initiated in a second region. In addition, preliminary efforts to disseminate and scale‐up aspects of the program to the full Cuban population have started.